ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF-EFFICACY SISWA PADA MATERI SPLDV - Yullia Ningtyas Disparrilla; Ekasatya Aldila Afriansyah (Universitas Muhammadiyah Makassar, 2022)
In general, students’ problem solving skills tend to be in a low category, this is shown by the number of students who have not been able to complete diagnostic tests given in the form of routine and non-routine problems. One of the factors that affect students’ mathematical problem-solving skills is self-efficacy. This study aims to find out students’ mathematical problem-solving and self-efficacy skills in the material of a two-variable linar equation system. The type of research used in this study is qualitative research. The research method used is a descriptive analysis method. The subjects in this study were grade VIII students of the 2020/2021 school year who were in Pakuwon Subdistrict, Garut Subdistrict, Garut Regency which numbered 6 students. The sampling technique in this study is a purposive sampling technique. The data collection techniques used are mathematical problem-solving skills tests, self-efficacy questionnaires, interviews, and field records. The data analysis techniques in this study are data reduction, data presentation, and conclusion drawing. The results showed that students’ problem-solving skills were at 75% with the high category and student self-efficacy was at 68% with the good category.